2018
DOI: 10.1001/jamasurg.2018.2602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Depth of Sedation in Older Patients Undergoing Hip Fracture Repair on Postoperative Delirium

Abstract: clinicaltrials.gov Identifier: NCT00590707.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
140
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 125 publications
(157 citation statements)
references
References 44 publications
12
140
1
Order By: Relevance
“…9 In short, no statistically significant difference in the incidence of postoperative in-hospital delirium was found between the groups, but a significant effect modification by level of comorbidity was observed, where lighter sedation was associated with lower in-hospital delirium incidence in patients with low preoperative comorbidity. 9 In this study, we report the following secondary pre-specified outcomes from the STRIDE trial: persistent delirium at 1 month; change in functional outcomes from preoperative baseline at 1 month and 1 yr follow-up; and mortality at 1 yr after surgery. In addition, exploratory analysis was performed to determine the independent risk factors for 1 yr mortality and return to prefracture ambulation level.…”
Section: Editor's Key Pointsmentioning
confidence: 78%
“…9 In short, no statistically significant difference in the incidence of postoperative in-hospital delirium was found between the groups, but a significant effect modification by level of comorbidity was observed, where lighter sedation was associated with lower in-hospital delirium incidence in patients with low preoperative comorbidity. 9 In this study, we report the following secondary pre-specified outcomes from the STRIDE trial: persistent delirium at 1 month; change in functional outcomes from preoperative baseline at 1 month and 1 yr follow-up; and mortality at 1 yr after surgery. In addition, exploratory analysis was performed to determine the independent risk factors for 1 yr mortality and return to prefracture ambulation level.…”
Section: Editor's Key Pointsmentioning
confidence: 78%
“…The Original Discussion continues to place emphasis on evaluating lines of research related to comorbidity, which was felt to be an important effect modifier in the prior reporting of the primary outcome of the STRIDE trial. 4…”
Section: Strengths Original Discussion: '1) the Study Was A Randomizementioning
confidence: 99%
“…STRIDE was originally powered for postoperative delirium (primary outcome), reported previously. 4 Although power calculations were performed for mortality (secondary outcome), the mortality incidence in each group (14%) was lower than the preliminary assumption (31.5%); in fact, the absolute risk reduction magnitude (15.5%) for which power was calculated was larger than the actual 1-yr mortality rate in either group. Accordingly, this secondary analysis was underpowered for detecting associations between sedative depth and mortality.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…For example, a recent randomised trial of EEG-driven anaesthetic management in hip fracture patients found that anaesthetic depth only impacted cognition in a relatively healthy subgroup (A Strategy to Reduce the Incidence of Postoperative Delirium in Elderly Patients [STRIDE]). 116 Future studies should explore alternative approaches for anaesthetic management, notably the use of the EEG waveform and spectrogram in combination, and be large enough to perform subgroup analyses to explore the likelihood of more vulnerable subgroups.…”
Section: Preventionmentioning
confidence: 99%